Application Of The Fixed Asset Depreciation Method At SD 102076 Juhar Village - Pranju Harlon Sinaga; Abdul Gani; Minasari Nasution (Sean Institute, 2025)
The aim of this research is to determine: Application of the Fixed Asset Depreciation Method at SD 102076 Juhar Village. The purpose of this research is to determine whether there are differences in the influence of depreciation methods in calculating the amount of depreciation of non-building tangible assets on reports. This research was conducted at a school. This type of research is a case study. Data was obtained by conducting interviews and documentation. The data analysis technique used is quantitative analysis technique. The data analysis method used is descriptive, where the information used is a transaction recap report. The results of the research show that it will occur more/less in 2022 in 2023. The data analysis method used is descriptive, where the information used is a recap report so that the school must make corrections in the month and year concerned.